(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article is devoted to the study of the history of the formation and development of youth vocabulary in the German and Russian languages, taking into account its morphological and semantic features. The main stages of the development of youth speech are examined, начиная from student and school slang of the 18th–19th centuries and ending with the modern stage of digital communication. Particular attention is paid to word-formation mechanisms, semantic transformations, and the influence of socio-cultural factors. The study employs a comparative approach, which makes it possible to identify both general patterns and language-specific features in the development of youth vocabulary.